THE COMPARISON OF TRANSLATION RESULTS OF A NARRATIVE TEXT USING GOOGLE TRANSLATE AND THE MANUAL TRANSLATION OF SECOND YEAR STUDENTS AT SMA NEGERI 15 BANDUNG - Ariakusumah, Muhamad Aldo (2017)
This research aims to find out the translation quality and translation procedures in Google Translate and Human Translation. There are ten samples of the texts quality based on the result of translation by the students class XI IBB at SMA Negeri 15 Bandung with the most frequently used in Google Translate is Word - for word translation procedure (68, 2%). Borrowing (1, 4%), and the most frequently used in Human Translation is Literal Translation (77.27%), Free Translation (13,63%), Adaptation (4,54%), Transference or Borrowing (4,54%). Google Translate is not relevant and suitable for the translation work conducted by the 11 grade students and also other translation work conducted by people who intend to translate a foreign language